Effectiveness of bimodal stimulation of the auditory-somatosensory system in the treatment of tonal tinnitus - Bolandi, Masoud; Javanbakht, Mohanna; Shaabani, Moslem; Bakhshi, Enayatollah (American journal of otolaryngology, 2024)
The dorsal cochlear nucleus (DCN) is the interaction site of auditory and somatosensory system inputs. According to the stochastic resonance theory, hearing loss increases the neural activity of the somatosensory system in the DCN and causes tinnitus. it is possible to modulate this neural hyperactivity by applying random noise through the auditory and somatosensory systems (bimodal stimulation). Therefore, this study aimed to investigate the effectiveness of the bimodal intervention based on the theory of stochastic resonance. The study divided 34 participants into unimodal and bimodal groups with 17 subjects in each. The bimodal group received customized acoustic stimulation along with transcutaneous auricular vagus nerve stimulation (tAVNS) and the unimodal group received customized acoustic stimulation along with tAVNS as a sham. The treatment sessions in both groups were 6 sessions and each session lasted for 20 min. The participants were evaluated before, immediately after, and one month after the completion of the intervention sessions, using the Tinnitus Handicap Inventory (THI) questionnaire and the mismatch negativity (MMN) test. After the intervention sessions, the results indicated a statistically significant decrease in THI scores and a significant increase in the MMN amplitude in the bimodal group compared to the unimodal group. No significant changes in MMN latency were observed between the two groups. These changes were stable in the one-month follow-up visit. Our study showed that bimodal stimulation is a better intervention option compared to unimodal stimulation. Bimodal stimulation may be an effective intervention method for some subjects with tinnitus, especially people with hearing loss who have tonal tinnitus. •Bimodal is more effective than unimodal intervention in the treatment of tinnitus.•MMN amplitude can be an objective tool for studying the tinnitus treatment process.•MMN latency is not useful in the objective assessment of tinnitus.